2022
DOI: 10.1002/adom.202201175
|View full text |Cite
|
Sign up to set email alerts
|

Broadband Chiro‐Optical Effects for Futuristic Meta‐Holographic Displays

Abstract: Futuristic holographic displays will essentially require broadband chiro‐optical effects for medical imaging, virtual reality, smart security, and optical encryption. However, conventional metasurfaces cannot provide such on‐chip realization of broadband chiro‐optical effects. Moreover, the simultaneous conversion of amplitude, polarization, and phase (APP) at optical wavelengths to introduce giant chirality has not been realized yet. In this paper, a planar all‐dielectric metasurface is proposed incorporating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 72 publications
0
51
0
Order By: Relevance
“…The careful selection of the optimal values for the structure provides the required results for maximum CD at the multiband NIR wavelengths. Hydrogenated amorphous silicon is used to design the structure with high refractive index and negligible extinction coefficient [59].…”
Section: Designed Methdologymentioning
confidence: 99%
“…The careful selection of the optimal values for the structure provides the required results for maximum CD at the multiband NIR wavelengths. Hydrogenated amorphous silicon is used to design the structure with high refractive index and negligible extinction coefficient [59].…”
Section: Designed Methdologymentioning
confidence: 99%
“…A lot of meta-reflectors and amplifies based on metals have also been presented in the literature [55][56][57]. Recently, Mai et al has demonstrated a 3D structure to reflect one handedness of circularly polarized light and absorbing the opposite handedness [58]. Moreover, to avoid the complex fabrication procedures, few works reported on single layer structures to design meta-mirror [59][60].…”
Section: Introductionmentioning
confidence: 99%
“…The nanoscale thickness and planar footprints of metasurfaces enable their fabrication using single-step lithography technologies and allow them to take full advantage of mature semiconductor industries. So far, the research community has demonstrated numerous high-performance metasurfaces exhibiting a chain of functionalities including beam shaping [26], high-resolution imaging [27][28][29], metaabsorbers [30][31][32][33], asymmetric light transmission [34][35][36][37], hologram projection [38][39][40][41][42][43][44], and structured light generation [45][46][47][48][49][50][51][52][53][54].…”
Section: Introductionmentioning
confidence: 99%